Gambaran Pengetahuan Ibu Hamil tentang Antenatal Care dengan Frekuensi Kunjungan Antenatal Care di PMB Siti Nurjannah Ngemplak Demak - Istikomah Istikomah; Kristina Maharani; Mudy Oktiningrum (Jurnal Rumpun Ilmu Kesehatan, 2025)
Antenatal care is the midwifery care midwives provide to pregnant women before the baby's birth to ensure positive outcomes for both the mother and the baby. This care involves establishing a trusting relationship with the mother, detecting complications that could threaten life, preparing for the baby's birth, and providing health education for the mother. This descriptive study investigated pregnant mothers’ cognition of antenatal care at Midwifery Clinician Siti Nurjannah Ngemplak Demak by overviewing the object. This study's population consists of primigravida pregnant women in their third trimester taken with saturated sampling or total sampling, resulting in a sample of 40 primigravida pregnant women in their third trimester. The instruments used in this study include a questionnaire on pregnant mothers' cognition about antenatal care and the Maternal and Child Health (KIA) book for pregnant mothers. The researchers analyzed the data using univariate methods that include: the characteristics of pregnant women, knowledge of pregnant women about antenatal care, and the frequency of antenatal care visits. The research findings reveal that 20 respondents, or 50%, possess the majority of high school education characteristics. In terms of employment, 26 respondents, or 65%, are employed. Most respondents were aged 20–35 years. In terms of education level, they had an average level of cognition, with a frequency of 18 respondents (45%). When it comes to the frequency of visits by pregnant women, most respondents complied, with 26 respondents (65%) reporting a visit frequency. The research findings suggest that motivating pregnant women about the importance of knowledge and antenatal care visits is a recommended strategy.